THE EFFECT OF PNEUMOCOCCAL CONJUGATE VACCINE PENTABIO, AND MULTI-INJECTION IMMUNIZATION EDUCATION ON KNOWLEDGE AND ACCEPTANCE OF MULTI-INJECTION IMMUNIZATION - Ayu Wulansari; Puspitasari , Dwiyanti; Ningtyas , Woro Setia (Indonesian Midwifery and Health Sciences Journal, 2024)
Background: Pneumonia is the main caused of morbidity and mortality in children under five years of worldwide. According to the Health Profile Data (2021), the province with the highest coverage of pneumonia among under-fives was in East Java (50%) and in Blitar Regency at 40%. Indonesia was tried to control pneumonia by increasing PCV immunization efforts. PCV immunization is first given at the age of two months along with pentabio immunization or known as multi injectable immunization. Based on the results of a preliminary study conducted at the Talun Primary Health Care in Blitar Regency on pregnant women in the 3rd trimester and mothers who have babies aged 0-2 months, it was found that 71% of mothers did not know about the existence of multiple immunization injections between pcv and pentabio. Knowledge about one's health can be done by providing health education. This study aims to analyze the effect of health education on knowledge of PCV immunization, pentabio and multi-injection immunization and acceptance of multi-injection immunization in respondents. Methods: This study used pre-experimental design with a one group pretest-posttest. The number of samples was 40 respondents with sampling techniques used purposive sampling. The independent variable was health education which was given once with lecture method. The dependent variable was knowledge and acceptance of multi-injection immunization. The instrument used was a questionnaire. Data analysis used Wilcoxon signed rank test and Mc Nemar test. Results: After providing education showed that the knowledge of respondents in the good category increased from 25% to 95%, in the sufficient category 5% and there were no respondents in the poor category. Acceptance of multiple immunization injections after providing education showed that respondents receiving multiple immunization injections increased from 30% to 97.5%. Wilcoxon signed rank test results p = ≤0.01 and Mc nemar test results p = ≤0.01, indicating  significant effect of pneumococcal conjugated vaccine, pentabio, and multi-injection immunization  education on knowledge and acceptance of multi-injection immunization. Conclusion: There is an effect of providing education on  pneumococcal conjugated vaccine, pentabio, and multi-injection immunization  on knowledge and acceptance of multi-injection immunization